Dynamics of social interactions during group formation in male of the cichlid fish Oreochromis mossambicus - Oliveira, Rui Filipe (2012)
After a period of social isolation all male group of O. mossambicus were observed for 5 days after which ovulated females were added. the frequency of different types of social interactions and behavioural activities along the observation period were recorded, and their patterns of temporal variation were studied. The relationships among the different variables were analysed using PCA. During the process of group formation the following regular temporal sequence of predominant activities was detected: (a) mutual assessement and hierarchy formation; (b) territorial establishment and nest digging; (c) courtship. We suggest that this results reflect the probable sequence of events during the process of lek formation in nature at the onset of each breeding period.